Optimized adenoviral vector that enhances the assembly of FMDV O1 virus-like particles in situ increases its potential as vaccine for serotype O viruses - Ziraldo, Micaela (2020)
Although replication-defective human adenovirus type 5 (Ad5) vectors that express in situ the capsid-encoding region of foot-and-mouth disease virus (FMDV) have been proven to be effective as vaccines in relevant species for several viral strains, the same result was not consistently achieved for the O1/Campos/Brazil/58 strain. In the present study, an optimization of the Ad5 system was explored and was proven to enhance the expression of FMDV capsid proteins and their association into virus-like particles (VLPs). Particularly, we engineered a novel Ad5 vector (Ad5[PVP2]OP) which harbors the foreign transcription unit in a leftward orientation relative to the Ad5 genome, and drives the expression of the FMDV sequences from an optimized cytomegalovirus (CMV) enhancer-promoter as well. The Ad5[PVP2]OP vaccine candidate also contains the amino acid substitutions S93F/Y98F in the VP2 protein coding sequence, predicted to stabilize FMD virus particles. Cells infected with the optimized vector showed an ∼14-fold increase in protein expression as compared to cells infected with an unmodified Ad5 vector tested in previous works. Furthermore, amino acid substitutions in VP2 protein allowed the assembly of FMDV O1/Campos/Brazil/58 VLPs. Evaluation of several serological parameters in inoculated mice with the optimized Ad5[PVP2]OP candidate revealed an enhanced vaccine performance, characterized by significant higher titers of neutralizing antibodies, as compared to our previous unmodified Ad5 vector. Moreover, 94% of the mice vaccinated with the Ad5[PVP2]OP candidate were protected from homologous challenge. These results indicate that both the optimized protein expression and the stabilization of the in situ generated VLPs improved the performance of Ad5-vectored vaccines against the FMDV O1/Campos/Brazil/58 strain and open optimistic expectations to be tested in target animals.